The tenants of East Harlem - Sharman, Russell Leigh, 1972- (Berkeley : University of California Press, 2006)
Rich with the textures and rhythms of street life, The Tenants of East Harlem is an absorbing and unconventional biography of a neighborhood told through the life stories of seven residents whose experiences there span nearly a century. Modeled on the ethnic distinctions that divide the community, the book portrays the old guard of East Harlem: Pete, one of the last Italian holdouts; José, a Puerto Rican; and Lucille, an African American. Side by side with these representatives of a century of ethnic succession are the newcomers: Maria, an undocumented Mexican; Mohamed, a West African e.
East Harlem -- Pleasant Avenue : the Italians -- 106th street : the Puerto Ricans -- 125th Street : the African Americans -- 116th Street : the Mexicans -- Third Avenue : the West Africans -- Second avenue : the Chinese -- Urban "renewal" and the final migration.
Includes bibliographical references (pages 229-236) and index.
Print version record.
English.
JSTOR
Keywords: Sociology, Urban -- New York (State) -- New York; Urban anthropology -- New York (State) -- New York; Ethnicity -- New York (State) -- New York; Community development, Urban -- New York (State) -- New York; Gentrification -- New York (State) -- New York; East Harlem (New York, N.Y.) -- Social conditions; East Harlem (New York, N.Y.) -- Economic conditions; East Harlem (New York, N.Y.) -- Social life and customs; Sociologie urbaine -- New York (État) -- New York; Anthropologie urbaine -- New York (État) -- New York; Ethnicité -- New York (État) -- New York; Développement communautaire urbain -- New York (État) -- New York; Embourgeoisement (Urbanisme) -- New York (État) -- New York; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Community development, Urban; Economic history; Ethnicity; Gentrification; Manners and customs; Social conditions; Sociology, Urban; Urban anthropology; New York (State) -- New York; New York (State) -- New York -- East Harlem